Orthogonal photon states manipulation using dark-bright soliton conversion control - Chaiyasoonthorn, Sawatsakorn; Mitatha, Somsak; Yupapin, Preecha P. (My University, 2011)
In this paper, we have derived and presented a new concept of multi orthogonal photon states generated by using dark-bright soliton collision within the modified add/drop filter, which it is known as PANDA ring resonator. By using the dark-bright soliton conversion control, the obtained outputs of the dynamic states can be used to randomly form the multi orthogonal photon pairs, which can be available for computer and communication security applications.
Keywords: Orthogonal photons; PANDA ring; Random code; Soliton control